PENGELOLAAN KEPERAWATAN NYERI PADA TN. W DAN TN. S DENGAN PASCA PROSTATECTOMY DI RSUD BATANG - Supriyo Supriyo; M. Projo Angkasa; Darohjatun Min Aeni (Poltekkes Kemenkes Semarang, 2021)
Background – Prostatic hyperplasi benign is a progresive enlargement of the prostate gland that can cause obstruction and disturbances in uretrhra. In Indonesia, Benigna Prostatic Hyperplasia ranks second after urinary tract stone disease, and in general, it is estimated that almost 50% of men in Indonesia aged over 50 years are found to suffer from BPH. Therefore, if seen, from more than 200 million people of Indonesia, it can be estimated that if 100 million men aged 60 years and over numbered 5 million people, it can be stated that approximately 2.5 million Indonesian men suffer from this disease.Objectives – this study aims to describe pain care nursing in post prostatectomy patients in Batang District Hospital.Research methods – research conducted using descriptive research methods with case studies. The subjects of this study were two were treated at Batang District Hospital, which were selected using a purposive sampling technique.Results – research results obtained on client I scale pain perceived scale 4 and the problem partially resolved, for client II scale paint felt client scale 3 and the problem is resolved. Keywords : Benign Prostatic Hyperplasia, Prostatectomy, Pain